Biogas Basics, Integrated Approaches, and Case Studies - El-Fatah Abomohra, Abd; Salama, El-Sayed (IntechOpen, 2022)
Anaerobic digestion is by far the most important technology for providing clean renewable energy to millions of people in rural areas around the world. It produces biomethane with anaerobic-digestate as a byproduct that can be used as a biofertilizer. In the context of energy consumption, more than 85% of the total energy consumed currently comes from non-renewable fossil resources. A wide variety of biowastes can be used as feedstocks for biogas production. Biogas technology can provide sustainable, affordable, and eco-friendly green energy along with useful byproducts. This book discusses the basics of biogas production and aims to address the needs of graduate and postgraduate students as well as other professionals through further evaluation of biogas production via case studies.